Implementation of Vibration and Wave Puzzles to Increase Students’ Interest and Motivation in Learning Physics Class - Pramesti, Hari Agusasi; Saputro, Adhi Harmoko (WaPFi (Wahana Pendidikan Fisika), 2025)
For students to develop interest and motivation in learning physics, teachers need to create active and enjoyable learning experiences. A suitable model is crucial to provide students with new ways to engage with physics, making them more active in class and improving their learning outcomes. This study aims to assess the effect of students’ interest and motivation on their learning outcomes, as well as their response to the applied learning model. Using a pretest and posttest experimental design, the study involved seventy 11th-grade students. Data were collected through tests and questionnaires. The learning outcomes (tests) were analyzed using paired t-test, while questionnaire data were examined using multiple linear regression with SPSS 25. The paired t-test results show a 2-tailed value of 0.000 indicating a significant increase in students’ motivation and interest due to the use of vibration and wave puzzles. Meanwhile, based on the analysis of the questionnaire results, the Adjusted R-Square value from the regression analysis is 0.456, which means that 45.6% of the variation in learning outcomes is explained by students’ interest and motivation. These findings shows that the developed learning model is effective in increasing students’ interest and motivation to learn towards students’ achievement or learning outcomes. Student engagement and performance from the application of this puzzle-based learning method makes learning active and learner-centered engagement in a fun and innovative way, offering an alternative approach to teaching physics and a foundation for further research on other physics topics.